Supplementing corn chips with mango cv.‘Ataulfo’peel improves their sensory acceptability and phenolic profile, and decreases in vitro dialysed glucose - Lopez Diaz, Jose Alberto (2020)
Mango processing discards phenolic‐rich by‐products. The present work evaluated the effects of supplementing corn chips with mango cv. “Ataulfo” peel (0, 10, 15, and 20%), regarding sensory acceptability, phenolic content, profile and in vitro bioaccessibility, antioxidant activity, and in vitro dialyzed glucose. Addition of up to 15% mango peel maintained or increased consumer acceptability. Phenolic content increased approximately nine‐fold (from 0.9 mg GAE/g for control chips, to 8.9 mg GAE/g for chips with 15% peel). Chips were enriched with mangiferin, quercetin and rutin, neither of which was found in control samples; antioxidant activity also increased significantly. Enriched chips had an increased bioaccessible (three‐fold) and dialyzable (two‐fold) phenolic content, and decreased in vitro dialyzed glucose. We conclude that “Ataulfo” mango peel improves sensory acceptability and phenolic content of supplemented corn chips, as well as increasing antioxidant capacity and reducing in vitro dialyzed glucose concentration, thereby exerting functional properties.